Fat-to-lean mass ratio as a new anthropometric indicator in predicting metabolic syndrome among Malay adolescents in Terengganu, Malaysia. (27th May 2022) - Lim, Jing Ying; Wee, Bee Suan; Mohamad, Marhazlina; Mhd Jalil, Abbe Maleyki; Shahril, Mohd Razif; Lua, Pei Lin
Background: Metabolic syndrome (MetS) is defined as a cluster of risk factors for predicting type 2 diabetes mellitus and cardiovascular disease. Objectives: This cross-sectional study aimed to develop a cut-off value for fat versus lean mass ratio (FLMR) in predicting MetS and to investigate the association between this indicator with MetS and its components. Methods: Subjects comprised 238 Malay adolescents (79% female) aged 18–19 years old. Anthropometric assessment comprised weight, height and waist circumference (WC). Body composition was measured using bioelectrical impedance analysis techniques while blood pressure was measured using a blood pressure monitor. Fasting blood glucose, total cholesterol, triglycerides, high-density lipoprotein cholesterol (HDL-c), and low-density lipoprotein cholesterol were determined from an overnight fasting blood sample. MetS was determined based on International Diabetes Federation (2007) definition for adolescents aged 16-year-old and above. Results: The prevalence of MetS was 2.1%. Receiver Operating Characteristics curve analysis revealed that the optimal cut-off value for FLMR was 0.441 with an Area Under the Curve of 0.874 (95% CI: 0.825, 0.913); with sensitivity of 80.0% and specificity of 71.0%. FLMR cut-off of 0.441 was associated with high WC ( p < .001), low HDL-c ( p < .001) and MetS ( p < .05). Binary Logistic Regression analysis revealed that adolescents with high WC, low HDL-c and MetS had higher odds of developing increased FLMR than the cut-off value with an odds ratio (OR) of 43.4 (95% CI: 9.7, 193.9), 4.7 (95% CI: 2.3, 9.8) and 13.3 (95% CI: 1.5, 121.2), respectively. Conclusion: FLMR possesses fair discriminatory ability in identifying MetS among adolescents and significant association exists between FLMR and MetS and some of its components.